Evaluation of Skin Damage from Accidental Removal of a Hemostatic Wound Clamp (The iTClamp). Issue 6 (24th August 2017) - Mckee, Jessica L.; Lakshminarasimhan, Prasanna; Atkinson, Ian; LaPorta, Anthony J.; Kirkpatrick, Andrew W.
Abstract: Background: Controlling bleeding early in the prehospital and military setting is an extremely important and life-saving skill. Wound clamping is a newly introduced technique that may augment both the effectiveness and logistics of wound packing with any gauze product. As these devices may be inadvertently removed, the potential consequences of such were examined in a simulated, extreme, inadvertent disengagement. Methods: The wound clamp used was an iTClamp (Innovative Trauma Care; Edmonton, Alberta, Canada) that was applied and forcefully removed (skin-pull) from the skin of both a human cadaver and swine. Sixty skin-pull tests were sequentially performed to measure the pull weight required to remove the device, any potential skin and device damage, how the device failed, and if the device could be re-applied. Results: Observations of the skin revealed that other than the expected eight small needle holes from device application, no other damage to the skin was sustained in 98.3% of cases. Conversely, of the 60 devices pulled, 93.3% of the devices sustained no damage and all could be re-applied. Four (6.7%) of the devices remained in place despite a maximum pull weight >22lb F (pound-force). The mean pull weights for pin bar pull were (lb F ): vertical 9.2 (SD=5.0); perpendicular 2.5 (SD=1.7); and parallel 5.3 (SD=3.1). For the encompassed pull position group, mean pull weights were (lb F ): vertical 5.7 (SD=2.3); perpendicular 3.0 (SD=2.5); and parallel 14.5 (SD=3.5). The overall mean for all groups was 6.7 (SD=5.2). The two main reasons that the iTClamp was pulled off were because the friction lock let go or the needles slipped out of one side of the skin due to the angle of the pull. Conclusion: Inadvertent, forcible removal of the iTClamp created essentially no skin damage seen when the wound clamp was forcibly removed from either cadaver or swine models in a variety of positions and directions. Thus, the risks of deployment in operational environments do not seem to be increased. JL Mckee, P Lakshminarasimhan, I Atkinson, AJ LaPorta, AW Kirkpatrick .Evaluation of skin damage from accidental removal of a hemostatic wound clamp (the iTClamp) .Prehosp Disaster Med .2017 ;32 (6 ):651 –656 .